Bladder lipoma: Moroccan case report - Omar Jendouzi; Younes Boukhlifi; 0thmane El houadfi; Amine Essaoudi; Mohamed Alami; Ahmed Ameur (The Pan African Medical Journal, 2020)

(untitled)
Lipomas are encapsulated benign tumors typically found in the integument, central nervous system or gastrointestinal tract and represent the most common benign mesenchymal neoplasm in adults. Bladder lipoma is a rare tumor that has been reported in a handful of cases in medical literature. A literature review from PubMed, MEDLINE, EMBASE and Cochrane databases of bladder lipoma yielded less than 20 cases. We report a case of a 69 year-old Moroccan male patient with hematuria as a chief symptom. The diagnosis of bladder lipoma was suspected by flexible fibroscopy and assessed by transurethral resection. Macroscopic and histological examination revealed a lipomatous tumour with no sign of malignancy. There was no recurrence after one year of follow-up. Although bladder lipomas are rare entities, they must be considered in the differential diagnosis of bladder tumor. However, we should always keep in mind that any bladder tumor is malignant until proven otherwise.